Prognostic significance of STING expression in solid tumor: a systematic review and meta-analysis - Kim, Younghoon; Cho, Nam-Yun; Jin, Lingyan; Jin, Hye Yeong; Kang, Gyeong Hoon (Frontiers in Oncology, 2023)
Objective: Stimulator of interferon genes (STING) is a key regulator in initiating innate immune response from sensing cytosolic DNA. Recent studies have revealed that cGAS-STING signaling pathway has a crucial role in tumor development and progression across cancer types. Herein, we conducted a meta-analysis to explore the relationship between the immunoexpression of STING and the survival outcome of patients in various solid tumors. Studies relevant to the subject was searched from PubMed, Embase, and Web of Science.Results: Eleven studies including 2,345 patients were eligible for the analysis. STING expression in tumor cells was related with improved disease-free survival/ recurrence-free survival (DFS/RFS) (HR = 0.656, 95% CI = 0.455-0.946, P = 0.024) but not with overall survival (OS) (HR = 0.779, 95% CI = 0.534-1.136, P = 0.194). STING expression in stromal cells, however, did not show significant correlation with DFS/RFS and OS (HR = 0.979, 95% CI = 0.565-1.697, P value = 0.940 and HR = 1.295, 95% CI = 0.845-1.985, P = 0.235, respectively). In a subgroup analysis, STING expression in tumor cells were associated with better DFS (HR = 0.622, 95% CI = 0.428-0.903, P = 0.012). In tumor cells, favorable DFS/RFS were also related with studies from univariate analysis and the gastrointestinal system (HR = 0.667, 95% CI = 0.482-0.923, P = 0.015 and HR = 0.566, 95% CI = 0.330-0.971, P = 0.039).Conclusions: STING expression in tumor cells are associated with favorable outcome in solid tumors.